Subspecies and Distribution. L.a.amurensisVinogradov,1924—fromETransbaikaliaandAmurRiverEalongthe SeaofOkhotskandacrossSchsofVerkhoyanskandCherskiyrangestoKolymaUpland(Russia). L. a. flavescens Vinogradov, 1925 — Kamchatka (Russia). in Cricetidae ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Subspecies and Distribution. L.a.amurensisVinogradov,1924—fromETransbaikaliaandAmurRiverEalongthe SeaofOkhotskandacrossSchsofVerkhoyanskandCherskiyrangestoKolymaUpland(Russia). L. a. flavescens Vinogradov, 1925 — Kamchatka (Russia). ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 292, DOI: 10.5281/zenodo.6707142 ...